Publicistinio stiliaus sakinio ilgis ir struktūra - Bitinienė, Audronė (Kalbotyra, 1995)
This investigation is based upon the statistical and comprehensive analysis of 12,000 sentences of publicistic style (newspapers). The distinctive feature of publicistic style in Lithuanian is the average length of sentences (13.5 words) and its parameters. In publicistic style very short (1-8 words) and short sentences (9-17 words) prevail (45,5% and 30,6%). Sentence length depends upon the frequency of simple and complex or compound sentences. In publicistic style simple sentences are more frequent (54,2%) than complex or compound ones. Sentence length and structure in publicistic style depend little upon sub-styles (variants) and the author’s individuality.In publicistic style the same tendencies of sentence development are characteristic of simple sentences and the constituent parts of compound and complex sentences.